MODERASI ISLAM BERBASIS TASAWWUF - Nadhif Muhammad Mumtaz (Sekolah Tinggi Agama Islam AL Aqidah Al Hasyimiyyah Jakarta, 2020)
Islamic moderation is one of the efforts to eradicate radicalism in Indonesia. However, until now the facts say that radicalism is still growing. Meanwhile, tasawwuf as a foundation for a Muslim to carry out his teachings moves to the roots of thoughts about understanding the religion. Therefore, Islamic moderation based on tasawwuf is expected to eradicate radicalism to its roots. This research is a qualitative research with a literature approach. Data collection was obtained through various literatures. The results of this study say that Islamic moderation based on Sufism is the moderation of Islam that Rahmatan lil Alamin walks in the middle road without oppressing the left or the right.